Synthesis and experimental investigation of V-CaCl2 composite desiccant for performance enhancement in evaporative cooling applications - Aydin, Devrim; Charidi, Mohammad; Khosravi, Nima (Sage Publications Ltd, 2020)
This study investigates novel vermiculite-calcium chloride composite solid desiccant material for desiccant-assisted evaporative cooling applications. In addition, comparative performance analyses between direct and desiccant-assisted evaporative cooling were performed. According to the study results, temperature drop around 10 celcius with an average cooling rate of 700 W and coefficient of performance in the range of 5-6 were obtained for both processes. The specific cooling capacity was found 3.5 kJ/g for desiccant assisted and 2.6 kJ/g for direct evaporative cooling process. It was concluded that at low air mass flow rates, performances of both processes are similar whilst at higher air flow rates, desiccant-assisted evaporative cooling becomes more efficient in terms of specific cooling capacity and coefficient of performance. The experiments also showed that vermiculite-calcium chloride provides effective moisture sorption rates above 40% air relative humidity levels. Therefore, this desiccant material could be suitable for desiccant-assisted evaporative cooling applications.
Keywords: Evaporative cooling; desiccant; vermiculite; calcium chloride; air-conditioning; experimental analysis